Patient involvement in priority-setting for medical research: A mini review of initiatives in the rare disease field - Katirai, Amelia; Kogetsu, Atsushi; Kato, Kazuto; Yamamoto, Beverley (Frontiers in Public Health, 2022)
Patient involvement (PI) in determining medical research priorities is an important way to ensure that limited research funds are allocated to best serve patients. As a disease area for which research funds are limited, we see a particular utility for PI in priority-setting for medical research on rare diseases. In this review, we argue that PI initiatives are an important form of evidence for policymaking. We conducted a study to identify the extent to which PI initiatives are being conducted in the rare disease field, the features of such initiatives, the trends in the priorities elicited, and the extent to which translation into policy is reported in the academic literature. Here, we report the results of this exploratory review of the English-language literature gathered through online databases and search engines, with the aim of identifying journal articles published prior to December 2020, describing PI initiatives focused on determining priorities for medical research funding in the rare disease field. We identified seven recently-published articles and found that the majority made use of structured methodologies to ensure the robustness of the evidence produced, but found little reported practical implementation or concrete plans for implementation of the results of the initiatives. We conclude that priority-setting initiatives are meaningful mechanisms for involving patients in determining research directions. However, we highlight the importance of translation into policy as a necessary next step to fully utilize the results and move beyond well-intentioned exercises. Finally, we draw attention to the benefits of involving patients throughout this process.